REVITALIZATION DISCIPLINE AS EFFORT CREATE ENVIRONMENT LEARN WHICH CONDUCIVE FOR STUDENT PUBLIC ELEMENTARY SCHOOL 1 SUMURUP - Muhammad Sobri; Dinda Nurhayati Sesariana Dewi (El Midad, 2023)
This research has a purpose to find out discipline student low grade in SDN 1 Sumurup, factors that influence student discipline, and strategies for increase discipline student. Deep method study This using descriptive qualitative method. Data collection was carried out through interviews, observation, as well as documentation. The data analysis used is reduction data, presentation data, And conclusion drawing. The results of this study include: 1) Sumurup 1 Public Elementary School has made the right rules to create a conducive learning environment but there are still students who have not been able to apply them. 2) The factors causing the lack of discipline of low grade students at SDN 1 Sumurup consist of internal and external factors. 3) Strategies to improve student discipline include: a) using self-management strategies (self-monitoring, stimulus control, and self-reward), b) making the teacher a role model for students in applying discipline, c) the teacher takes a personal approach on a one-by-one basis with students, d) implementing a reward and punishment system, e) providing counseling and assistance to students who are experiencing problems, f) promoting socialization regarding discipline in schools to students and parents, and g) evaluating changes in student behavior.